Jesus vandag: Moontlikhede van Ernst Troeltsch se Christologie - Botha, Pieter J. J. (Hervormde teologiese studies, 1988)
Jesus today: Possibilities of the Christology of Ernst Troeltsch The significance of the historical Jesus for faith is a major issue in the debate concerning the value of theology. Ernst Troeltsch constructed a meaningful answer to both questions in terms of what he called Glaubenslehre. A discussion of his views on the value of Jesus for faith is placed in the context of his theological system. Although Troeltsch sees Jesus' significance in symbolic terms he emphasises the need for historical study, without which a symbol becomes empty. A short critical discussion of Troeltsch's significance to the contemporary debate on Christology concludes the essay.